Novel (Hetero)arylalkenyl propargylamine compounds are protective in toxin-induced models of Parkinson's disease. Issue 1 (December 2016) - Baranyi, Mária; Porceddu, Pier; Gölöncsér, Flóra; Kulcsár, Szabina; Otrokocsi, Lilla; Kittel, Ágnes; Pinna, Annalisa; Frau, Lucia; Huleatt, Paul; Khoo, Mui-Ling; Chai, Christina; Dunkel, Petra; et al.
Abstract Background Mitochondrial dysfunction, oxidative stress and their interplay are core pathological features of Parkinson's disease. In dopaminergic neurons, monoamines and their metabolites provide an additional source of reactive free radicals during their breakdown by monoamine oxidase or auto-oxidation. Moreover, mitochondrial dysfunction and oxidative stress have a supraadditive impact on the pathological, cytoplasmic accumulation of dopamine and its subsequent release. Here we report the effects of a novel series of potent and selective MAO-B inhibitory (hetero)arylalkenylpropargylamine compounds having protective properties against the supraadditive effect of mitochondrial dysfunction and oxidative stress. Results The (hetero)arylalkenylpropargylamines were tested in vitro, on acute rat striatal slices, pretreated with the complex I inhibitor rotenone and in vivo, using the 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) induced acute, subchronic, and chronic experimental models of Parkinson's disease in mice. The compounds exhibited consistent protective effects against i) in vitro oxidative stress induced pathological dopamine release and the formation of toxic dopamine quinone in the rat striatum and rescued tyrosine hydroxylase positive neurons in the substantia nigra after rotenone treatment; ii) in vivo MPTP-induced striatal dopamine depletion and motor dysfunction in mice using acute and subchronic, delayed application protocols. One compound (SZV558) was also examined and proved to be protective in a chronic mouse model of MPTP plus probenecid (MPTPp) administration, which induces a progressive loss of nigrostriatal dopaminergic neurons. Conclusions Simultaneous inhibition of MAO-B and oxidative stress induced pathological dopamine release by the novel propargylamines is protective in animal models and seems a plausible strategy to combat Parkinson's disease.